2014
DOI: 10.1186/1477-7819-12-275
|View full text |Cite
|
Sign up to set email alerts
|

Coblation plus photodynamic therapy (PDT) for the treatment of juvenile onset laryngeal papillomatosis: case reports

Abstract: BackgroundIn treating juvenile-onset laryngeal papillomatosis, the most difficult aspect is preventing recurrence. After a single treatment, recurrence can begin after as soon as 20 days and the recurrent rate can be higher than 90%. The causes of recurrence include the presence of mucosal cells infected with papilloma virus, which are undetectable with the naked eyes, and surgery-induced infection. Photodynamic therapy (PDT) could effectively solve this problem. Virus-infected cells have a very high metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…This finding is concordant with previous reports of low-risk HPV 6 and 11 being the types of HPV most frequently detected in the larynx. 34 It is clear that recurrences occur in patients with RRP because of the persistence of HPV DNA. Because all patients were free of lesions after the initial treatment with MVA E2, biopsy samples were not taken for PCR analysis after the first round of injections.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concordant with previous reports of low-risk HPV 6 and 11 being the types of HPV most frequently detected in the larynx. 34 It is clear that recurrences occur in patients with RRP because of the persistence of HPV DNA. Because all patients were free of lesions after the initial treatment with MVA E2, biopsy samples were not taken for PCR analysis after the first round of injections.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic procedures involve exposing the larynx with a laryngoscope and using low temperature plasma technology to visualize the tumor resection, as the effects of plasma technology can reduce post-operative laryngeal edema and reduce intraoperative metastasis [7].…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, ROS can influence cell signaling . PDT has been used to treat laryngeal papillomas, precancerous lesions, and malignancies, and has achieved promising clinical results . Previous studies have reported that treatment of laryngeal carcinoma with PDT induced good healing of vocal folds.…”
Section: Introductionmentioning
confidence: 99%
“…A popular second‐generation photosensitizer, 5‐aminolevulinic acid (5‐ALA) has been used in the treatment of laryngeal keratosis and papillomatosis . We selected 5‐ALA as the photosensitizer in our study.…”
Section: Introductionmentioning
confidence: 99%